Legal Protection of the Right to Freedom and Personal Integrity of the Citizens of Ukraine (Private and Public Aspect) - Hrynko, Svitlana; Hrynko, Ruslan; Levytskyi, Maksym; Makovskyi, Artem; Bilovskyi, Oleksandr (The Age of Human Rights Journal, 2024)
The article defines the specifics of private legal protection of the right to freedom and personal inviolability of an individual in Ukraine. It elaborates on the content of the right to freedom and personal inviolability of a natural person, including both physical and psychological inviolability. The article identifies methods that violate the psychological inviolability of an individual (hypnosis, polygraph, etc.). Private legal protection of the right to freedom and personal inviolability, characterized as a personal non-property right of a natural person, has been analyzed in the context of legal regulations. The conclusion has been drawn that the right to freedom and personal inviolability is safeguarded through the establishment of a set of prohibitions regarding its infringement and methods of protection in case of violation. Both private legal and public legal means of protecting the right to freedom and personal inviolability of a natural person have been identified. The article characterizes violations of the right to freedom and personal inviolability of an individual in the context of their placement in places of liberty deprivation (orphanages, psychiatric hospitals, boarding schools, military guard-houses, detention facilities, etc.). Through the analysis of Ukrainian judicial practice and the European Court of Human Rights, the conclusion has been drawn that there are cases where there are no legal grounds for placing individuals in places of liberty deprivation, as well as instances of torture, cruel, inhuman, and degrading treatment of these individuals.